Consumer Adoption of Virtual Reality in Indonesia Through Lens of Diffusion of Innovation Theory and Technology Acceptance Model - Regianto Wisnuseputro; Dina Dellyana (Green Publisher Indonesia, 2025)
This research explores the prospective adoption of Virtual Reality technologies in the Indonesian consumer market by identifying key factors and constructs that influence the consumer adoption in Indonesia. The study considers the successful efforts of Virtual Reality technology manufacturers to create consumer-level hardware within the price range of household electronic devices. In this case, we measure the willingness of the Indonesian mass consumer market to adopt this technology. Quantitative survey analyzed using the combined framework of Diffusion of Innovation Theory and Technology Acceptance Model is used for this study. The study concludes that Observability and Social Influence are the major factors of new technology adoption in the Indonesian consumer market, among others. In general, Indonesia consumer market has good attitude towards future Virtual Reality technology adoption. Therefore, it is recommended that any attempts to capture the Indonesian market by Virtual Reality manufacturers consider these factors. A Go-To-Market strategy applying the learnings from this study is also provided within this study.